RENDAHNYA KADAR VITAMIN D BERPENGARUH PADA JUMLAH TH 17 PASIEN LUPUS ERITEMATOSUS SISTEMIK - Wira Daramatasia (Jurnal Ilmiah Kesehatan Media Husada, 2018)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease that is more frequently found with a high mortality rate . Aetiopathogenesis of the disease is unclear, although it has been demonstrated abnormalities of various immune cells including T cell hyperreactivity, B cells , dendritic cells , and decreased function of regulatory T cells (Treg). Vitamin D has a role in the immune system regulation, but in patients with SLE is still a lot of controversy. This study aims at funding out the correlation of vitamin D level with the percentage amount of Th17 cells in patients with SLE. Observation Laboratory in the form of a cross -sectional study with blood sampling SLE patients and healthy control in RSSA . Of the total 48 SLE patients and 23 healthy controls , this study compared the amount (percentage) of Th17 cells by looking at level of vitamin D. SLE patient's vitamin D level was measured by ELISA method , the amount of the percentage of Th17 cells (CD4+, IL17+) was measured by using a BD FACSCalibur flowcytometri method. The mean levels of vitamin D of SLE patients compared to healthy controls differed significantly (p = 0.00). There are significant differences in the number of Th17 percentage (p = 0.04), and Tukey test results between the control group of SLE patients with hypovitamin D (p = 0.03) . There is no correlation between vitamin D status with Th 17 cells (P = 0.22 and r= -0,33). Conclusion, It is concluded that 1,25(OH)2D3 affects the cell life cycle stages . This effect could contribute substantially to reduce the activation of T cells in inducing Th cell development 17 . therefore by providing therapy vitamin D (analog 1,25 (OH) 2D3) can modulate the treatment of autoimmune diseases , particularly SLE patient